Single-parent families in Tuva and Kazakhstan: a statistical and demographic view of the problem - Rostovskaya, Tamara K.; Natsak Органа Д.; Elamanova, Ainur S. (The New Research of Tuva, 2024)
The article presents a comparative analysis of the statistical and demographic characteristics of single-parent families in Tuva (Russia) and Kazakhstan at the present stage. It considers the key factors that influence the prevalence of these families. The sources used are the All-Russia Population Censuses of 2010 and 2020, as well as the National Population Censuses of the Republics of Kazakhstan in 2009 and 2022. The article also uses materials on current demographic statistics, including gender characteristics, fertility rates, life expectancy, marriage patterns, divorce rates, and economic situations and income stratifications of different family types in Tuva and Kazakhstan. As a result of socio-demographic transformations, both Tuva and Kazakhstan have seen an increase in single-parent households, but the proportion of nuclear single-parent households in Kazakhstan is higher than in Tuva. The quantitative gender differentiation in the structure of the modern population is more pronounced in Tuva compared to Kazakhstan, which in turn affects the marriage structure of the population. In Kazakh society, the rate of marriage is higher than in Tuvan society. In Tuva, the proportion of unregistered marriages is more than double that of Kazakhstan, which has a negative impact on the quality of family life for the population. It has been shown that there are significant differences in the structure and typology of reasons for the formation of single-parent households in Tuva and Kazakhstan. Public censure and stigmatization of illegitimate births and single parenthood are more common in Kazakh society. Both societies have a high birthrate, but there are significant differences in out-of-wedlock and adolescent fertility rates, which lead to the formation of single-parent families. These rates are higher in Tuva. Divorce is equally common in both regions, leading to single-parent households. These families are at risk of poverty and social instability, especially for those raising multiple children, children with disabilities, or with a low level of education.